Community Participation in School Prospects and Challenges - Matin, Kashif; Ahmad, Arshad Ikram (JOURNAL OF INDIAN EDUCATION, 2019)
The present paper has been written with the objective of providing the prospects and challenges of community participation in school. The entire paper is divided into three parts. The first part deals with the introduction, concept and definition of community, participation and community participation in school. The second part deals with Indian perspective of community participation in school, where the historical background, success story of SSA, Rashtriya Madhyamik Shiksha Abhiyan (RMSA) and Right To Education (RTE) has been discussed. In the third part, issues and challenges related to community participation in school have been discussed, followed by a conclusion.